Bladder Dysfunction in Iranian Patients with Multiple Sclerosis - Azadvari, Mohaddeseh (J Multidiscip Healthc, 2020)
BACKGROUND: Bladder dysfunction is one of the most disabling problems in multiple sclerosis patients, associated with lower quality-of-life and social isolation. There have been few studies regarding bladder dysfunction in Iranian patients with multiple sclerosis. Therefore, this study was designed to assess bladder dysfunction in Iranian patients with multiple sclerosis. METHODS: This cross-sectional study was conducted in the MS Clinic of Sina Hospital (affiliated to Tehran University of Medical Sciences) between January 2019 and January 2020. Patients were asked to fill the valid and reliable Persian version of the 8-item Actionable Bladder Symptom Screening Tool (ABSST) questionnaire. Demographic data and accompanying symptoms such as fatigue, depression, anxiety, bowel dysfunction, urinary problems and walking status were recorded. RESULTS: Two hundred and twenty-eight cases were enrolled. One hundred and eighty-three were female (80.3%) and 45 (19.7%) were male (F/M ratio=4). The mean ABSST score was 6.8±5.7. Based on the cut-off value of eight, 83 (28.8%) had actionable bladder symptoms (36.4%). The mean age and duration of the disease were significantly higher in the group with ABSST≥8. The number of patients with urinary retention, dribbling, and incontinence was significantly higher in the second group, while the number of individuals who could walk without help was significantly higher in the first group (ABSST<8). Logistic regression analysis by considering an ABSST score of less or more than 8 as dependent and age, sex, duration of the disease, marital status, education level, and BMI as independent variables showed that age, education level, and duration of the disease are independent predictors. CONCLUSION: According to these results, nearly one-third of Iranian patients with MS suffer from an overactive bladder, which should be considered by physicians.